THE LETHAL EURO CRISIS: NOT THE GLOBAL FINANCIAL CRISIS BUT THE EUROZONE GOVERNANCE IS RESPONSIBLE - Soltes, Dusan (European Scientific Journal, ESJ, 2015)
The paper deals with some experiences as gathered from our research in the area of the European Integration within the EU in general and with the current handling of the ongoing global economic and financial crisis in particular. That in addition to various other negative impacts on the Internal market of the EU has brought with itself also a direct thread to the very existence of its common currency Euro and the entire Eurozone and finally also the EU itself. The paper in more details presents some of the main reasons for these negative development and impact on Euro. It analyses some of the hectic and unsystematic reactions and measures as taken by the EU institutions in order to save its common currency from a total collapse and/or its splitting into two â€œsub-currenciesâ€ as a stronger north and weaker south Euro currencies, Eurozone extra â€œgovernmentâ€, etc. That all after the decade long total ignorance of the Maastricht Treaty and its convergence criteria for the common currency. If its criteria have been observed strictly by all Euro zone members including of course also by Germany and France and/or otherwise all being penalized including those latter ones by the EU institutions there would be no such a deep crisis of Euro as it has been going on for already more than seven years.